Length of life inequality around the globe. - Smits, J; Monden, C (2009)
Inequality in the distribution of adult length of life - defined as age at death in the population aged 15 and over - is studied for virtually all countries of the world using a new database with over 9000 life tables covering a period of up to two centuries. The data reveal huge variation among countries and time periods in the degree to which the available years of life are distributed equally among the population. Most length of life inequality (about 90%) is within-country inequality. Our findings make clear that measures of length of life inequality should be adjusted for life expectancy to get a more relevant indicator of length of life differentials across populations. At similar levels of life expectancy, substantial differences in inequality are observed, even among highly developed countries. Expressed as premature mortality, inequality may be 35-70% higher in the most unequal countries compared to the most equal ones. Countries that reached a certain level of life expectancy earlier in time than other countries, and countries that improved their life expectancy more quickly than others, experienced higher levels of inequality.